On Nonlinear Fractional Relaxation Differential Equations - Tate, Shivaji; Kharat, V. V.; Gandhi, M. A. (Communications in Mathematics and Applications, 2023)
In this paper, by using the Krasnoselskii fixed point theorem and the Banach fixed point theorem, we prove the existence and uniqueness of solutions for a class of nonlocal Cauchy problem for nonlinear Caputo fractional relaxation differential equations. Finally, one illustrative example is given to demonstrate our results.
Keywords: Fixed points; Fractional relaxation differential equations; Mittag-Leffler; Existence; Uniqueness